PENGARUH CUSTOMER PERCEIVED VALUE DAN PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMBELIAN ULANG MELALUI BRAND EXPERIENCE (Studi Pada Konsumen Sepeda Motor Honda Tipe Bebek Di Kecamatan Pedurungan, Semarang) - Reski Pratiwi; Naili Farida; Bulan Prabawani (Universitas Diponegoro, 2015)
Along with the times, the need for the transportation is also more increasing. Motorcycle became transportation that most in demand by the people of Indonesia as a means of supporting the daily activities. Honda is one of the famous motorcycle brand in Indonesia. It has been years that Honda became the market leader which has never shifted from its position at the top as a motorcycle manufacturer that most widely sold its products. However, in the period of 2009-2013 the sales of Honda motorcycles types of cub decreased. The purpose of this study is to determine the effect of customer perceived value and perceived quality towards repeat purchasing decision through variable brand experience on consumers of Honda motorcycles cub type at Pedurungan, Semarang. This research is explanatory research type approach uses towards 100 respondents with a sampling technique multistage sampling. The type of data collection of this study are using the technique of questionnaires, interviews and literature methods. The analysis technique used was qualitative and quantitative. Quantitative analysis using validity test, reliability test, correlation coefficient, simple and multiple regression analysis, the coefficient of determination, a signification test (t test and F test), path analysis and also use the help application programs IBM SPSS Statistics 20.0. The result of this research approved that customer perceived value (X1) and perceived quality (X2) partially or simultaneously can influenced brand experience (Y1) and repeat purchasing decision (Y2). According the result of path analysis showed that brand experience variable is not intervening variable towards repeat purchasing decision in this research.